Escola em projeto: trajetórias e construções da tutela educacional entre os Potiguaras da Paraíba - Freire, Arthur Ramalho (2021)
This work aims to analyze the educational projects in which the Potiguaras were submitted, especially from the SPI period onwards. This is a research in the archives made available by FUNAI and in the SPI's online collection available at the Museu do Índio. Therefore, the work provides a description of the collected documents and discusses the educational projects of religious missions, official bodies and other educational institutions that were within the circuit circumscribed in the indigenous territory. Indigenous populations start to give new meaning to the schools of these education projects in which they will always look for ways to resist the silencing of their identities. The documentation and literature consulted place the tutelary practices in the context of the different political and social moments in which the Potiguaras indigenous populations were inserted. The trajectories analyzed show the resistance and struggle of the Potiguaras in the face of these tutelary projects, as well as the unfolding of these processes from the colonial period to the present day, in view of the public policies implemented after the 1988 constitution.